Macedonio poeta recienvenido - Jorge Monteleone (Cuadernos LIRICO)
This essay vindicates Macedonio Fernández as a “poeta recienvenido”, a “newcomer poet” that, at the same time, denies any autobiographical essentialism yet builds in the poem “Elena Bellamuerte” the imaginary transfiguration of a central autobiographical fact : the death of his wife Elena de Obieta. The poetry of Macedonio occupies in his literature the place of the neutral (from the Latin ne-uter, neither one nor the other, but between two poles, in an undecided position). The neutral character of his poetry is both a radicalization of the ghost of the beloved and a protest and a cancellation of death transfigured by fiction in the poem, in which Elena is “la niña del fingido morir” (the fake dead girl) and death is denied by love, and is considered only an “occultation”. Poetry is thus an act of “Belarte Conciencial”, that manifests itself in the neutral imaginary : neither life nor death, neither you nor I, neither the absence nor the presence, neither time nor place, neither one nor the other but in between two terms, the undecided place where All-Mystery is not named, but is waiting for the Eternal.